Level and slope of volatility smiles in Long-Run Risk Models - Nicole Branger; Paulo Rodrigues; Christian Schlag (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2017)
We propose a long-run risk model with stochastic volatility, a time-varying mean reversion level of volatility, and jumps in the state variables. The special feature of our model is that the jump intensity is not affine in the conditional variance but driven by a separate process. We show that this separation of jump risk from volatility risk is needed to match the empirically weak link between the level and the slope of the implied volatility smile for S&P 500 options.
urn:nbn:de:hebis:30:3-450645
Keywords: G12; 330; asset pricing; Epstein-Zin preferences; jump risk; stochastic volatility; level and slope of implied volatility smile